Long term monitoring of cold-water coral growth shows response to episodic meteorological events in the NW Mediterranean. (June 2020) - Chapron, L.; Le Bris, N.; Durrieu de Madron, X.; Peru, E.; Galand, P.E.; Lartaud, F.
Abstract: Lophelia pertusa and Madrepora oculata, two cosmopolitan coral species of the deep ocean, build reef-like structures that provide ecological niches and nurseries for many species. These cold-water corals (CWCs) are thought to grow slowly making associated communities vulnerable to disturbance. However, in situ growth dynamics remains poorly known. The aim of this study was thus to quantify the growth rates of L. pertusa and M. oculata and their variability in relation to environmental conditions that are expected to influence their physiological functions. Such data can be useful to ground-truth physiological rates and improve the prediction of their sensitivity to global change. As part of a long-term monitoring programme of the Lacaze-Duthiers canyon in the Northwestern Mediterranean Sea, fragments of the two species were repeatedly sampled and redeployed at 530 m depth, from November 2010 to May 2018. Budding rates and linear extensions of L. pertusa and M. oculata were hence quantified and their inter-annual variability documented. The data were analyzed in relation to in situ monitoring of water temperature, current speed and turbidity. This study presents the longest in situ survey of the growth patterns of L. pertusa and M. oculata . The observations revealed a strong inter-annual variability in growth rates, both for L. pertusa and M. oculata, and suggest an influence of hydrological conditions on the growth dynamics. Particularly, as regard to episodic water plumes events such as NW wind-induced dense water shelf cascades and E-SE storm-induced downwellings in autumn-winter. In this study, three types of responses were observed: (i) high budding rates but low colony linear extension for strong water plume events periods (ii) high budding rates and high linear extension associated to organic matter supply during medium intensity water plume events, and (iii) low budding rates, low linear extension and high mortality due to high sedimentation rates in the absence of water plume event. Lophelia pertusa appears to be more resilient to these hydrological changes. Disturbance of the regional circulation patterns, in addition to longer-term change in water mass properties such as warming, deoxygenation and acidification, are thus important parameters to consider for CWC reef stability. This is particularly important since increased storminess, and decreased cascading/downwelling intensities, are predicted to occur within the next century. Graphical abstract: Image 1 Highlights: We conducted a temporal in situ growth study of deep corals for eight years. Corals live in a Mediterranean canyon subject to episodic water plumes events. Strong inter-annual variability in growth rates with the hydrological conditions. The absence of water plumes impacts dramatically the growth of corals.